2019
DOI: 10.1111/pace.13796
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of postprocedural anticoagulation in high‐risk patients undergoing WATCHMAN device implantation

Abstract: Background Left atrial appendage closure (LAAC) is an alternative to long‐term anticoagulation for thromboembolic protection in patients with atrial fibrillation (AF) and high bleeding risk. Short‐term Warfarin use following LAAC is well‐studied, while data pertaining to novel oral anticoagulant (NOAC) use in this setting is less robust. Specifically, data regarding the safety and efficacy of postprocedural NOAC use in high‐risk patients is lacking. Objective To compare the safety and efficacy of Warfarin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
(22 reference statements)
1
17
0
Order By: Relevance
“…Initial studies of the WATCHMAN device excluded patients with past history of ICH as these studies had a long-term warfarin arm and a short course of warfarin was used for LAAC (typically ∼45 days for the WATCHMAN) to allow for device endothelialization to prevent thrombi formation on the device surface. 93 However, studies have demonstrated noninferiority with NOACs for short-term anticoagulation post LAAC, 93,94 and dual antiplatelet therapy can be used as an alternative to short-term anticoagulation postprocedurally. 95,96 It is important to note the difference between short term (∼six weeks post LAAC) anticoagulation versus lifelong anticoagulation as the risk of ICH increases over years.…”
Section: Ich Risk Stratification and Risk Reductionmentioning
confidence: 99%
“…Initial studies of the WATCHMAN device excluded patients with past history of ICH as these studies had a long-term warfarin arm and a short course of warfarin was used for LAAC (typically ∼45 days for the WATCHMAN) to allow for device endothelialization to prevent thrombi formation on the device surface. 93 However, studies have demonstrated noninferiority with NOACs for short-term anticoagulation post LAAC, 93,94 and dual antiplatelet therapy can be used as an alternative to short-term anticoagulation postprocedurally. 95,96 It is important to note the difference between short term (∼six weeks post LAAC) anticoagulation versus lifelong anticoagulation as the risk of ICH increases over years.…”
Section: Ich Risk Stratification and Risk Reductionmentioning
confidence: 99%
“…Four studies 13,14,25,35 used two different antithrombotic regimens after LAAO. Therefore, each of these four studies was considered to include two research groups, and finally, 36 research groups were included in the analysis.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Nevertheless, both groups had statistically significant differences in the mean CHADS2 (2.4 vs 2.1), CHA2DS2-VASC (4.1 vs 3.8), and HASBLED (2.7 vs 2.4) scores between the warfarin and NOAC groups, respectively. 5 Cohen et al, 6 in this issue of PACE compared the safety and efficacy of Warfarin and NOAC (mainly apixaban) use in a high-risk patient population undergoing LAAC with the Watchman device. Albeit this is a retrospective study, all patients were well-matched with regard to age, gender, comorbid conditions, prior bleeding events, thromboembolic risk, and bleeding risk, with a significant difference only in the proportion of patients with a history of congestive heart failure, and prior falls.…”
Section: Noacs Versus Vkas During Watchman Implantation In Patients Wmentioning
confidence: 99%
“…At 245 days, there were three patients in the warfarin group and one in the NOAC group that met the criteria for a composite endpoint of stroke or death (event rate 7.0% vs 2.1%; P = .35). 6 This study is limited by a relatively small sample size, which may also lead to the study being underpowered to detect events such as DRT and stroke. As with any nonrandomized, retrospective study without propensity matching, selection bias is possible.…”
Section: Noacs Versus Vkas During Watchman Implantation In Patients Wmentioning
confidence: 99%
See 1 more Smart Citation